Partially encased section: strength and stiffness under fire conditions - Piloto, P.A.G. (2018)
Fire resistance of partially encased sections (HEB and IPE) depends on the temperature evolution during fire exposure. Eurocode 4, part 1.2 [1], proposes the assessment of the cross section using the method of the four components under fire (flanges, web, concrete and reinforcement). This study aims to assess the balanced summation model of Eurocode (informative annex G) with respect to the plastic resistance to axial compression and the effective flexural stiffness of the cross section with respect to the weak axis. New formulae will be proposed to evaluate fire resistance, based on new simple formulas to determine the flange average temperature, the residual height and average temperature of the web, the residual cross section and average temperature of concrete, the reduced stiffness and strength of reinforcement. The advance calculation method was used to validate new and safe formulae, based on the analysis of the cross section totally engulfed in fire.